2019
DOI: 10.7150/thno.34947
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular therapeutics to treat the side effects induced by a depolarizing neuromuscular blocking agent

Abstract: Succinylcholine (Sch) is the only depolarizing neuromuscular blocking agent widely used for rapid sequence induction in emergency rooms. Unfortunately, a variety of (sometimes lethal) adverse effects, such as hyperkalemia and cardiac arrest, are associated with its use, and currently there are no specific antidotes to reverse Sch or to treat these side-effects. Methods: The binding behaviors of Sch and several synthetic receptors, including cucurbit[7]uril, sulfo-calix[4]arene and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 82 publications
0
36
0
3
Order By: Relevance
“…Succinylcholine (Sch, Figure 1 ) is the only depolarizing NMBA that is widely used for rapid sequence induction in emergency rooms 90 . However, its use can be accompanied by severe side-effects, such as hyperkalemia and cardiac arrest.…”
Section: Pillararenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinylcholine (Sch, Figure 1 ) is the only depolarizing NMBA that is widely used for rapid sequence induction in emergency rooms 90 . However, its use can be accompanied by severe side-effects, such as hyperkalemia and cardiac arrest.…”
Section: Pillararenesmentioning
confidence: 99%
“…Among these hosts, WPA 6 exhibited excellent antidotal effects. In vivo studies showed that the encapsulation of Sch by WPA 6 reduced the guest side-effects', such as the incidence of cardiac arrhythmia, high serum potassium levels, and muscular damage 90 . Inspired by the success of sugammadex, Stoikov and co-workers synthesized a water soluble PA 5 , namely WPA 5 (Figure 2 B), containing similar side-chains as those of sugammadex, and aimed at achieving a better reversal effect for the use of rocuronium bromide.…”
Section: Pillararenesmentioning
confidence: 99%
“…Hamilton et al berichteten über eine Reihe potenter C4A-basierter Wachstumsfaktor (Platelet-Derived Growth Factor,PDGF)-Antagonisten (163)(164)(165)(166)(167)(168)(169)(170)(171)(172)(173)(174)(175)(176)(177), die in der Lage sind die Ty rosinphosphorylierung des PDGF-stimulierten PDGF-Rezeptors (PDGFR) zu inhibieren. [158] CAs wurden entwickelt, um an die Drei-Schleifen-Region von PDGF zu binden und dessen Interaktion mit PDGFR zu stçren.…”
Section: Krebswirksame Eigenschaftenunclassified
“…Diese Verbindung weist jedoch zahlreiche Nebenwirkungen wie Myalgie und prolongierte Apnoe auf. [166] Wang et al verwendeten supramolekulare Therapeutika zur Behandlung dieser Nebenwirkungen und setzten 31 ein, das starke Affinitäten zu Sch zeigte.In einem Sch-überdosierten Mausmodell, wurde 31 unmittelbar nach Sch-Administration injiziert. Die Gesamtüberlebensraten stiegen signifikant an, was auf eine erfolgreiche Detoxifikation hinweist.…”
Section: Detoxifikationunclassified
“…The most prominent examples include amphiphilic cyclodextrins, calixarenes and pillararenes as non-viral vectors for gene condensation, membrane permeation and targeted delivery. Zhang et al 15 studied the use of synthetic supramolecular receptors such as cucurbit[7]uril, sulfo-calix[4]arene and water-soluble carboxylatopillar[6]arene (WP6) to evaluate the antidotal effect of neuromuscular blocking agent succinylcholine (Sch). Among these, WP6 with high binding affinity towards Sch was able to reverse Sch induced depolarization and reduce the efflux of intracellular potassium.…”
mentioning
confidence: 99%